Perovskite solar cells with atomically coherent interlayers on SnO2 electrodes - Min, Hanul; Lee, Do Yoon; Kim, Junu; Kim, Gwisu; Lee, Kyoung Su; Kim, Jongbeom; Paik, Min Jae; Kim, Young Ki; Kim, Kwang S.; Kim, Min Gyu; Shin, Tae Joo; Il Seok, Sang (Nature (London), 2021)
In perovskite solar cells, the interfaces between the perovskite and charge-transporting layers contain high concentrations of defects (about 100 times that within the perovskite layer), specifically, deep-level defects, which substantially reduce the power conversion efficiency of the devices 1 – 3 . Recent efforts to reduce these interfacial defects have focused mainly on surface passivation 4 – 6 . However, passivating the perovskite surface that interfaces with the electron-transporting layer is difficult, because the surface-treatment agents on the electron-transporting layer may dissolve while coating the perovskite thin film. Alternatively, interfacial defects may not be a concern if a coherent interface could be formed between the electron-transporting and perovskite layers. Here we report the formation of an interlayer between a SnO 2 electron-transporting layer and a halide perovskite light-absorbing layer, achieved by coupling Cl-bonded SnO 2 with a Cl-containing perovskite precursor. This interlayer has atomically coherent features, which enhance charge extraction and transport from the perovskite layer, and fewer interfacial defects. The existence of such a coherent interlayer allowed us to fabricate perovskite solar cells with a power conversion efficiency of 25.8 per cent (certified 25.5 per cent)under standard illumination. Furthermore, unencapsulated devices maintained about 90 per cent of their initial efficiency even after continuous light exposure for 500 hours. Our findings provide guidelines for designing defect-minimizing interfaces between metal halide perovskites and electron-transporting layers. An atomically coherent interlayer between the electron-transporting and perovskite layers in perovskite solar cells enhances charge extraction and transport from the perovskite, enabling high power conversion efficiency.